The impact of e-marketing orientation and learning capacity on online SME performance in Jordan: The moderating role of technological orientation - Aljabari, Mohammed; Althuwaini, Sulaiman; Qudah, Omar Al; Bouguerra, Asma (Asian Development Policy Review, 2024)
The purpose of the study is to investigate the effects of electronic marketing orientation (EMO) as well as learning capability (LC) on the performance of internet-based SMEs in Jordan using the moderating role of technological orientation (TO). To achieve this goal, the research employed a non-probability sample method and a study-adapted questionnaire. We distributed 320 surveys to Internet small and medium enterprises (SME) owners using the Internet-based survey method (Google Form), which adhered to a probabilistic random sample approach, resulting in 156 entirely complete responses. We subsequently examined the data using the Smart PLS. The study's findings indicate that TO moderates the statistically significant connection among EMO, LC, and internet-based SME performance. In contrast, EMO and LC had a statistically important effect on internet-based SME performance. According to this study's final finding, learning ability is an indicator of the performance of online SMEs. In addition to outlining numerous significant consequences for owners of online SMEs, this report also makes several recommendations for further studies. Based on prior findings, the researchers propose that marketing managers in enterprises focus on the use of several e-marketing channels, such as email advertising, Facebook advertising, YouTube promotion, and TikTok promotion, to develop stronger market positioning for SMEs. Furthermore, future studies may take into account some fresh factors, including staff expertise, SME managers' and owners' technological prowess, and an emphasis on innovation when assessing the performance of online SMES firms.